Correction: Recent advances in material design and reactor engineering for electrocatalytic ambient nitrogen fixation. (4th March 2022) - Ali, Tariq; Muhammad, Niaz; Qian, Yijun; Liu, Sisi; Wang, Sai; Wang, Mengfan; Qian, Tao; Yan, Chenglin
Abstract : Correction for 'Recent advances in material design and reactor engineering for electrocatalytic ambient nitrogen fixation' by Tariq Ali et al., Mater. Chem. Front., 2022, DOI: ; 10.1039/d1qm01620b .